Hydrogeologic and geomorphic settings of the Lower Subansiri Basin, Assam, India - Goswami, U.; Patgiri, A. D.; Sarma, J. N. (Journal of Nepal Geological Society, 2002)
Geomorphic settings of an area provide valuable supplementary information regarding groundwater recharge, their occurrence and distribution. The geomorphic settings of the Lower Subansiri Basin can broadly be represented by three distinct geomorphic units viz., structural hills, piedmont zone and alluvial plain. While the elevation, slope, lithology, drainage pattern and various relevant morphometric parameters vary from one geomorphic unit to another, the conditions of recharge and discharge, occurrence and distribution of groundwater also differ in different units. The structural hills occupying only 4.5% of the area along the north-western boundary represent a high run-off zone characterised by steep slope and fairly dense parallel to sub-parallel drainage. The piedmont zone, built up by the coalescence of alluvial fan deposits, represents 7.7% of the area occurring in a long and narrow NE-SW trending steeply sloping belt along the foothills of Arunachal Pradesh. Owing to high permeability, this zone hardly retains any water and hence forms a high recharge zone with relatively deeper groundwater level. The alluvial plain, covering 87.8% of the basin area and characterised by a gentle slope, serves both as recharge and discharge areas where groundwater occurs relatively close to the ground surface. Panel diagrams prepared for the Lower Subansiri Basin showing the thickness and extent of granular zones display that the unconsolidated alluvial sediments are primarily composed of sands of various grade and gravel with minor amounts of silt and clay. The sand-gravel isolith maps showing the cumulative thickness of the granular zones down to the depth of 40 m reveal that the subsurface formations in a major part of the alluvial plain of the Lower Subansiri Basin are entirely represented by granular zones. The granular zone in most parts of the area forms one single aquifer system where groundwater mostly occurs under unconfined to semi unconfined conditions. Due to the presence of thin clay and/or sandy clay lenses at shallow depths, however, the single aquifer system gets locally dissipated into multiple aquifer system where, barring the uppermost aquifer, groundwater mostly occur under semiconfined to confined conditions. The overall regional variation of depth to water level, from the piedmont zone in the north and north-west to the alluvial plain of the south and southeast, is controlled by the prevalent geomorphic settings of the area. The disposition of water table contours of the area indicates that the configuration of groundwater table closely controls to that of general topography of the area. The steeper hydraulic gradient observed to be present in the north and north-east indicates the possible control of the characteristically distinguished geomorphic setting, i.e., topography, relief and lithology.